2018
DOI: 10.1002/jsfa.9049
|View full text |Cite
|
Sign up to set email alerts
|

A practical toxicity bioassay for vicine and convicine levels in faba bean (Vicia faba)

Abstract: BCNU-sensitized red blood cells provide an ideal model for favism blood, to assess and compare the toxicity of faba bean varieties and their food products. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Those results suggest that vc-faba bean varieties are potentially safe for patients who are lacking G6PD, but further studies with more patients are required [205]. Moreover, new analytical procedures have been developed to quantify vicine and convicine in food products to assure food safety [71,206,207].…”
Section: Favismmentioning
confidence: 99%
“…Those results suggest that vc-faba bean varieties are potentially safe for patients who are lacking G6PD, but further studies with more patients are required [205]. Moreover, new analytical procedures have been developed to quantify vicine and convicine in food products to assure food safety [71,206,207].…”
Section: Favismmentioning
confidence: 99%
“…e percentage of this hemolysis is correlated with the G6PD deficiency levels as noticed in Table 1. Getachew et al previously demonstrated that fava bean aglycones cause an irreversible rapid GSH depletion with a simultaneous increase in oxidized glutathione (GSSG) production in G6PD enzyme defective human RBCs [24]. is was correlated with progressive accumulation of denatured hemoglobin products into high molecular weight (HMW) proteins and the formation of both band 3 membrane proteins and hemichromes as HMW protein aggregates [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Traditional means of estimating V-C contents are expensive and require highly sophisticated equipment. Recent efforts have led to the successful development of a new biological test (bioassay) and laboratory methods to detect V-C content in faba bean (2). These methods are relatively inexpensive and can have a turn-around time of as little as one week.…”
Section: The Importance Of V-cmentioning
confidence: 99%